Overview of Triglyceride levels in Lipemic Serum using Polyethylene Glycol (PEG) 6000 - Sugiah Sugiah; Kurniawan Dewi Budiarti; Astari Nurisani; Gina Nafsa Mutmaina; Alya NSY (Institute Of Computer Science (IOCS), 2023)
Lipemic causes interference with wavelength and light scattering caused by the presence of lipid particles. This study aims to determine the description of triglyceride levels in lipemic serum with and without the addition of polyethylene glycol (PEG) 6000. This type of research is experimental. The research conducted was descriptive research. The samples used were lipemic serum totaling 30 samples with triglyceride levels above 300 mg/dl. The results of the data analysis showed a mild lipemic level of 22 samples with an average of 379.00 mg/dl, a moderate lipemic level of 5 samples with an average of 558.40 mg/dl, and a severe lipemic serum of 3 samples with an average of 943.40 mg/dl. Based on the results of triglyceride levels without the addition of PEG 6000, the average level is 465.33 mg/dl, while the results of triglyceride levels using PEG 6000, the average level is 243.23 mg/dl. Based on the difference in triglyceride levels before and after adding PEG 6000, namely at the mild level, the average is 215.00 mg/dl (56%), at the moderate level, the average is 261.00 mg/dl (46%), and at the severe level, the average is 212.30 mg/dl (22%). It can be concluded that there are differences in triglyceride levels in lipemic serum before and after adding PEG 6000.